JASMINE: A SELF-EXPLANATORY WOMEN PROTAGONIST IN BHARATI MUKHERJEE’S JASMINE - Jeyappriya, Dr.P. (International Journal of Psychosocial Rehabilitation, 2020)
Bharati Mukherjee is one of the accomplished Diasporic writers. Her writing focuses mainly on women’s suppression, struggle to overcome the problems and attempt to attain identification. In Jasmine, Mukherjee tries to unravel the complicated layers of cross-cultural clashes through a series of adventures in which the protagonist takes during her odyssey from Punjab to California via Florida, New York and Lowa. Jasmine is the one of the most celebrated novels of the Mukherjee which represents a powerful woman who refuses to live with others. In fact this article is based on the assumption that “education” can make women more intelligent and comprehend things in a better fashion. Jasmine knowledge gives her the confident to face all the problems in life. It only makes her to get mingle with American life style. The knowledge of the outer makes to accept the transformation she has faced in her life without any guilty consciousness.